Evaluation of the effect of growth conditions on lipid production by Papiliotrema laurentii UFV-1 in culture media containing xylose - Santos, Raquel Cristina Vieira dos (2017)
Biofuels are an alternative to reduce dependence on fossil fuels. Among them, the biodiesel produced from the transesterification reaction between an alcohol and a triacylglycerol molecule is a substitute for conventional diesel. Edible vegetable oils are currently used as a source of triacylglycerols in the biodiesel production. Nevertheless, its production from these oils competes with food production for both arable lands and water. In addition, the vegetable oil features are affected by climatic conditions. These drawbacks can be circumvented by using alternative oil sources such as microbial oil. Oleaginous yeasts accumulate at least 20% of their dry weight as lipids, mainly in the form of triacylglycerols, nevertheless, superior values can be achieved depending on the culture conditions. Papiliotrema laurentii UFV-1, contrary to the oleaginous yeast model Yarrowia lipolytica, is capable of growing and accumulating lipids from xylose, the main sugar found in hemicellulose. Therefore, this work aimed to evaluate the effects of pH, C/N ratio, agitation speed, initial cell density and temperature on lipid production by P. laurentii UFV-1, a new yeast strain isolated from soil. We performed the centered face central composite design, with 25 combinations between the factors studied and three replicates at the central point, to evaluate their effects on the response variable lipid content. The highest lipid content (41.26%) was obtained in the following condition: pH equal to 7, C/N ratio equal to 70, agitation speed equal to 300 rpm and initial cell density equal to 0.8. Nevertheless, it was not possible to determine in this work the optimal condition for lipid production. In the condition afore mentioned, the fatty acid profile of P. laurentii UFV-1 was determined: 0.55% C14:0, 26.31% C16:0, 8.05% C18:0, 0.57% C20:0, 10.57% C16:1,45.5% C18:1, 0.36% C20:1,0.18% C18:3 and 17.19% C18:2. This profile is similar those found for soybean oil. Since this edible oil is currently used for biodiesel production, we conclude that lipid extracted from P. laurentii UFV-1 are suitable for its production.